Accountability, Competence, and Accounting Information Systems on the Performance of Private Schools - Seprida Hanum Harahap; Maya Sari (International Journal of Business Economics (IJBE), 2023)
Quality human resources in the implementation of education, of course, will make it easier for schools to achieve the goals set, one of which is to improve school performance. While the specific objectives are to identify Accountability, Competence, Accounting Information Systems, and mformulateModel of Private School Performance Improvement in Medan City. This research is a basic research (basic research). The first activity, is to identify the Private School Performance Improvement Model in Medan City. The second activity is compiling a Model for Improving the Performance of Private Schools in the City of Medan. To obtain certain data such as to find out the problems faced, the method of focus group discussion (focus group discussion) is used. The population in this study are those who play a role in improving school performance involving the school, namely the principal and school treasurer, who are in Private Upper Middle School in Medan City. Data collection techniques were carried out by means of documentation studies, interviews and questionnaires. The data analysis method used in this study is the SPSS method.